Mokyklų media centrai - Mozūraitė, Vita (Information & Media, 1997)
The years 1960 to 1975 represented a period of big growth for school libraries in the United States. It is obvious that a multitude of factors influenced this growth. During the last three decades the school library media centers (SLMC) became a unified media system whose basic purpose was to provide essential resources and services for the improvement of teaching and learning. The SLMC functions within the context of the educational system. In order to function effectively library media personnel should be aware of the school curriculum and teaching methods and also inspire teachers to use SLMC in their work. Only the school with the "problem-solving" teaching methods and resource-based learning can effectively organize teachers’ cooperation with SLMC personnel. Also SLMC has to be well equipped to provide students and teachers with the essential media and information resources - printed as well as non-printed. Special standards, directions and indications help to organize the work of SLMC and its personnel.